Wychowanie do wartości w zmieniającym się świecie - Świtała , Ireneusz M. (Studia Edukacyjne, 2019)
The need for value-oriented upbringing is obvious and necessary, though difficult in the world full of contrasts, conflicts and plurality of worldviews. Upbringing to values is aimed at preparing children and young people to individual, conscious selection and hierarchization of values and being guided by them in all areas of their personal and professional lives. Axiological education helps to gain the ability to distinguish between good and evil, truth and falsehood, selfishness and altruism. A pedagogical approach to values has become the subject of many scientific considerations and discussions among parents and teachers. This article is a review of the relationships between value systems and upbringing.